PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS4 PADA POKOK BAHASAN HIDROKARBON DI SMA/MA - Wulandari, Putri Adita; ', Herdini; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to develop learning media by using Adobe Flash CS4 software on the subject of Hydrocarbons at Chemistry Education study program. The result of this study is a product of learning media in the form of tutorial CD for hydrocarbon subject at Chemistry Education study program which has contents as follows: the determination of carbon atom C and H, the classification of hydrocarbons, the structure of alkane, alkyne and alkune, isomers, and the reaction of the hydrocarbon compounds. This study used Research and Development (R&D) method with ADDIE model which has five stages of development; they are analysis, design, development, implementation, and evaluation. The development model was modified by the writer only until the development stage. The result of validation test showed that learning media on the subject of Hydrocarbons is good with the result of validation by media experts 88.5% and material experts 92.5%, so the developed learning media is properly used on the learning and teaching process. The result of the development still has to be tried out at the students in teaching and learning process before it is used on a wider scale.Key Words : Development of learning media, Adobe Flash CS4, Hydrocarbon